I Care, If You Care: A Customizable Methodology for Eliciting Task Criticality Ratings to Guide Critical Task Analysis. (September 2022) - Willoughby, Hannah; Foley, Liam; Scipione, Andrea; Banbury, Simon
In this practitioner paper, we present a customizable multi-domain methodology for eliciting task criticality ratings to determine if a Critical Task Analysis (CTA) is required to analyze safety-critical tasks undertaken by personnel conducting uranium mining and processing. This evidence-based methodology builds upon previous methodologies by integrating empirical findings from the risk and job analysis literature. Tasks are rated against five critical criteria: Impact on Environmental/Social License, Mission Effectiveness, Impact on Human Health/Safety, Cost, and Impact on Equipment/Infrastructure. The relative importance of each criterion can be customized through pre-determined weightings. Based on the summation of ratings against each criterion, a task criticality rating is derived using a custom flowchart. This allows for wide applicability to projects and industries, whose weighting against each criterion will differ, and is a step towards creating a validated, standardized CTA methodology that can be applied by practitioners across a broad range of safety critical domains.